Challenges in Hazardous Waste Management: A Case Study of Talang Gulo Landfill in Jambi City - Nisa, Muflihatun; Ridwan, M; Azhary, Muhammad Rifqi (Formosa Journal of Multidisciplinary Research, 2024)
The improper storage of Hazardous and Toxic Waste (HTW) at the Talang Gulo Landfill prompted a study to analyze the implementation of Hazardous and Toxic Waste Management (HTWM). The study used a qualitative case study approach involving interviews, observations, and document analysis. 10 informants were selected through purposive sampling. The findings revealed several issues including a lack of trained personnel, limited budget, inadequate Standard Operating Procedures (SOPs), insufficient storage facilities, non-compliance with Personal Protective Equipment (PPE) use, and poor supervision. These findings highlight the need for the development of SOPs, worker training, facility upgrades, and improved supervision to enhance HTWM at the Talang Gulo Landfill.